Conformationally controlled ultrafast intersystem crossing in bithiophene systems. Issue 19 (3rd May 2018) - Skov, Anders B.; Larsen, Martin A. B.; Liisberg, Mikkel B.; Hansen, Thorsten; Sølling, Theis I.
Abstract : Bithiophenes serve as model systems for polythiophenes used in solar cell applications and molecular electronics. Bithiophene has two major conformations, where the disfavored cis -conformation shows a higher rate of intersystem crossing. Abstract : Bithiophenes serve as model systems for larger polythiophenes used in solar cell applications and molecular electronics. We report a study of ultrafast dynamics of two bithiophene systems measured with femtosecond time-resolved photoelectron spectroscopy, and show that their intersystem crossing takes place within the first few picoseconds after excitation, in line with previous studies. We show that the intersystem crossing rate can be explained in terms of arguments based on symmetry of the S1 minimum energy geometry, which depends on the specific conformation of bithiophene. Furthermore, this work shows that the minor cis -conformer contributes to an even higher intersystem crossing rate than the major trans conformer. The work presented here can provide guiding principles towards the design of solar cell components with even faster formation of long-lived excited states for solar energy harvesting.